Automatic Fill in the Blank Question with Distractor Generation Using NLP - Agrawal, Arpit; Shukla, Pragya; Panicker, Aishwarya; Dhawe, Trisha (International Journal of Computer Sciences and Engineering, 2019)
Today, in the advancement of Information Technology, machine learning has many applications especially in the field of Natural Language Processing. Thus with the help of NLP and algorithms of machine learning, we can automatically generate fill in the blank questions. Thus the task of manually constructing questions is no more a burden. An algorithmic approach has been deduced in this model to generate fill in the blank questions. A paragraph will be provided from which we have to select sentences with relevant content so that these sentences can be considered as options to generate fill in the blanks. The sentences with meaningful information are chosen for question generation. The questions will have relevant blanks which can be filled by one amongst the four choices provided just like multiple choice questions. Each question will have only one choice as the correct answer. The rest of the three choices will be wrong answer known as distractors.